Kierunki przemian rodziny w percepcji przedstawicieli dwóch pokoleń: seniorów i generacji Z - Strykowska-Nowakowska, Justyna (Pedagogika Społeczna Nova, 2024)
he paper concerns the issue of family transformations in the contemporary world. It is an important subject, as these transformations are visible in the daily observation of social life. The paper consists of two parts: theoretical and exploratory. The first presents considerations about traditional and modern perspective of the families taken by various researchers. The second presents qualitative research conducted in two groups: seniors and Generation Z. The obtained results show the differences and similarities in the views and expectations of the studied groups.